Iatrogenic intraprosthetic dislocation after closed reduction of dual mobility total hip arthroplasty: Report of two cases. (2020) - Rotini, Marco; Cianforlini, Marco; Aucone, Daniele; Pacetti, Emanuele; Politano, Rocco
Highlights: Dual mobility THA is widely appreciated for its lower rate of dislocation. These implants can experience intraprosthetic dislocation between head and PE liner. Intraprosthetic dislocation can result from maneuvers during closed reduction. Greater attention should be paid when treating dislocated dual mobility THAs. Abstract: Introduction: Among hip arthroplasty, dual mobility aims to improve ROM and reduce dislocation rates, however this particular implant can fail in specific ways. Iatrogenic intraprosthetic dislocation (IPD) is a rare occurrence that can happen during closed reduction of a dislocated dual mobility total hip arthroplasty. Presentation of Case: #1 – A 34-year-old male who came to our attention with an undiagnosed IPD. He had experienced a classic dislocation 6 days earlier, which was treated with closed reduction. CT-scan confirmed decoupling of the metal head and PE liner. #2 – An 89-year-old male came to our attention for THA dislocation. During closed reduction manouvers he suffered IPD of the implant. Both patients were treated with revision surgery. Discussion: Despite being already reported in literature, IPD are still not well known to practitioners and sometimes overlooked even by orthopaedic specialists. Given the good results and diffusion of this kind of implant, iatrogenic IPD in the contest of a classic dislocation might become more frequent in the clinical practice. Conclusion: When performing reduction maneuvers for a dislocated dual mobility total hip arthroplasty, X-rays must be carefully inspected for signs of IPD which, if undiagnosed, can lead to major implant damage and the need for extensive revision surgery.